Common and small molecules as the ultimate regulatory and effector mediators of antigen-specific transplantation reactions - Holan, Vladimir; Krulova, Magdalena (World journal of transplantation, 2013)
In spite of intensive research, the molecular basis of allograft and xenograft rejection still remains not fully understood. The acute rejection of an allograft is associated with the intragraft Th1 cytokine response, while tolerance of an allograft or xenograft rejection is accompanied by a higher production of the Th2 cytokines interleukin (IL)-4 and IL-10. Nevertheless, these cytokines are not the final regulatory and effector molecules mediating transplantation reactions. Data indicate that the functioning of common molecules with enzymatic activities, such are inducible nitric oxide synthase (iNOS), arginase, heme oxygenase-1 (HO-1) or indoleamine-2,3-dioxygenase (IDO), the bioavailability of their substrates (L-arginine, tryptophan, heme) and the cytotoxic and regulatory actions of their small gaseous products (NO, CO) can be the ultimate mechanisms responsible for effector or regulatory reactions. Using models of transplantation immunity and tolerance we show that T cell receptor-mediated recognition of allogeneic or xenogeneic antigens as well as the balance between immunity/tolerance induces distinct cytokine production profiles. The ratio between Th1 and Th2 cytokines efficiently regulates the expression of genes for common enzymes, such as iNOS, arginase, HO-1 and IDO. These enzymes may compete for substrates, such as L-arginine or tryptophan, and the final product of their activity are small molecules (NO, CO) displaying effector or regulatory functions of the immune system. Thus, it is suggested that in spite of the high immunological specificity of transplatation reaction, the ultimate players in regulatory and effector functions could be small and common molecules.